Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd005091.pub2
|View full text |Cite
|
Sign up to set email alerts
|

One dose per day compared to multiple doses per day of gentamicin for treatment of suspected or proven sepsis in neonates

Abstract: One dose per day compared to multiple doses per day of gentamicin for treatment of suspected or proven sepsis in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…This is in agreement with previously published data [4,13,14]. Lower C peak could potentially impair the efficacy, due to failure in achieving desired ratio of the C peak and minimum inhibitory concentration (MIC).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with previously published data [4,13,14]. Lower C peak could potentially impair the efficacy, due to failure in achieving desired ratio of the C peak and minimum inhibitory concentration (MIC).…”
Section: Discussionsupporting
confidence: 92%
“…Results of some studies indicate that the administration of gentamicin once daily causes minor discrepancies in minimal (C trough ) and/or maximal (C peak ) concentrations from the desired therapeutic range. Based on the results of a number of studies, the use of gentamicin by oncedaily regimen in neonates was as effective and safe as traditional dosing [4,5], whereas Croes et al showed restricted nephro-and cochleo-toxicity with preserved efficacy upon administration of aminoglycosides once daily [6].…”
Section: Introductionmentioning
confidence: 99%
“…Gentamicin is considered a valuable drug for treating sepsis and Pseudomonas infections, but the high dosages required can induce ototoxicity and nephrotoxicity. 36,37 Therefore, controlled release of gentamicin may decrease undesirable side effects. Furthermore, nanoparticle and microparticle preparations have the potential to be used in aerosol delivery and may enhance the therapeutic effectiveness and dose control of this and other aminoglycosides for treating pulmonary infections.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that many of the antibiotics approved for use in neonates have been licensed for so long that the emergence of bacterial resistance is being observed or suspected, underpinning the tendency to move to off-license alternatives. daily dosing of the total daily dose, with a reduced lower risk of toxicity [38,39]. Similarly, amoxicillin, licensed in children at a recommended dose of 40-50 mg/kg/day, proved to be effective against Streptococcus pneumoniae strains with relative resistance to penicillin when used at higher dose (80-90 mg/kg/day) without concomitant increase in the incidence of adverse events [40,41].…”
Section: Discussionmentioning
confidence: 99%